PENGARUH DIFFERENSIASI PRODUK dan HARGA TERHADAP KEPUTUSAN PEMBELIAN MELALUI PENDEKATAN PARTIAL LEAST SQUARE SEM SMARTPLS - Ahmad Saepul Anwar; Dodi Siswanto Siswanto (KarismaPro, 2020)
The purpose of this study aims to examine and analyze the influence between product differentiation and price on consumers Waroeng SS branch of Jatinangor.Population in this research is consumer Waroeng SS branch of Jatinangor  with the total sample of 100 respondents. Data analysis method used is descriptive and verifikatif method with quantitative approach. The instrument test is done by validity test and reliability test. The analytical technique used is path analysis, used to show relationships that show how much influence a particular variable either direct or indirect influence on some other variables.  The result of this study shows that partially and simultaneously of the product differentiation and price has a positive and significant effect on purchase decision. The partially of purchase decision influenced by product differentiation is 26,7%, and influenced by price is 25,75%. The amount of total influence by product differentiation and price on purchase decision is indicated by the magnitude of the coefficient of determination r2=0,518 or 51,80%, and influenced beyond the other variables is 48,20%. The conclusion of this study is product differentiation and price have positive and significant influence to purchasing decision, with the most dominant variable is product differentiation as variable that affected purchase decision at Waroeng SS branch of Jatinangor.The purpose of this study aims to examine and analyze the influence between product differentiation and price on consumers Waroeng SS branch of Jatinangor.Population in this research is consumer Waroeng SS branch of Jatinangor  with the total sample of 100 respondents. Data analysis method used is descriptive and verifikatif method with quantitative approach. The instrument test is done by validity test and reliability test. The analytical technique used is path analysis, used to show relationships that show how much influence a particular variable either direct or indirect influence on some other variables.  The result of this study shows that partially and simultaneously of the product differentiation and price has a positive and significant effect on purchase decision. The partially of purchase decision influenced by product differentiation is 26,7%, and influenced by price is 25,75%. The amount of total influence by product differentiation and price on purchase decision is indicated by the magnitude of the coefficient of determination r2=0,518 or 51,80%, and influenced beyond the other variables is 48,20%. The conclusion of this study is product differentiation and price have positive and significant influence to purchasing decision, with the most dominant variable is product differentiation as variable that affected purchase decision at Waroeng SS branch of Jatinangor.